2012
DOI: 10.3389/fgene.2012.00020
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Fluctuation Induced by Virus Infection Differs between MD-resistant and -susceptible Chickens

Abstract: Marek’s disease (MD) is a lymphoproliferative disease induced by Marek’s disease virus (MDV) infection. To augment vaccination measures in MD control, host genetic resistant to MD becomes obviously more and more important. To elucidate the mechanism of MD-resistance, most of researches were focused on the genetic differences between resistant and susceptible chickens. However, epigenetic features between MD resistant and susceptible chickens are poorly characterized. Using bisulfite pyrosequencing method, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…In addition to genetic differences, epigenetic differences now have been found to commonly exist between the two lines of chickens. A significant portion of genes that have been assessed differ in DNA methylation level at CpG sites within the CpG islands of promoter regions between the line 6 3 and 7 2 chickens [38][39][40][41][42]. Difference in microRNA expression was also detected using chicken microRNA array between the two lines of chickens [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to genetic differences, epigenetic differences now have been found to commonly exist between the two lines of chickens. A significant portion of genes that have been assessed differ in DNA methylation level at CpG sites within the CpG islands of promoter regions between the line 6 3 and 7 2 chickens [38][39][40][41][42]. Difference in microRNA expression was also detected using chicken microRNA array between the two lines of chickens [37].…”
Section: Discussionmentioning
confidence: 99%
“…Using miRNA microarray, it was demonstrated that miRNAs were differentially expressed between line 6 3 and 7 2 chickens post MDV challenge [37]. DNA methylation level at the promoter region of genes was also found being different between line 6 3 and 7 2 chickens with or without MDV challenge [38][39][40][41][42]. The objective of this report is to document the phenotypic differences of MD incidence for the two highly inbred lines 6 3 , 7 2 , and the series of RCS, to probe the genetic and epigenetic variability primarily for the lines 6 3 and 7 2 , and together to elucidate the genetic and epigenetic variation between the inbred lines that may be responsible, in part, for the phenotypic differences of MD incidence and vaccine protective efficacy at macroscopic level.…”
Section: Introductionmentioning
confidence: 97%
“…Our previous studies revealed that DNMTs were differentially expressed in the line 6 3 and line 7 2 chickens, 14 especially at 21 DPI, when the virus was reactivated from the latent stage. 6,15,16 The results point to a profound distinction between epigenetic profiles and expression of selected genes in line 6 3 and 7 2 chickens. The interesting finding that many of these differences, particularly in response to MDV challenge, affect genes of the immune system or tumor progression and related pathways provides a strong rationale for pursuit of our hypothesis that epigenetic signatures are associated with resistance or susceptibility of MDV induced tumorigenesis.…”
Section: Introductionmentioning
confidence: 87%
“…DNMTs were found to be differentially regulated in line 6 3 and 7 2 after MDV infection, suggesting that promoter methylation alterations are triggered by the infection. 6 DNA methylation was lost at active promoters in MDV carrying T cell lines and MD tumors, and was present in some CpG regions in MDV genome. 6 However, conclusions from these studies were limited since they focused on methylation variations at specific loci.…”
Section: Dnmt Gene Expression and Methylome In Marek's Disease Resistmentioning
confidence: 99%
See 1 more Smart Citation